Perlindungan Hukum terhadap Pekerja Migran Indonesia: Antara Regulasi dan Realitas di Lapangan - Aris Suliyono; Syafiuddin, Afif (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Legal protection for Indonesian Migrant Workers (PMI) remains a strategic issue in the context of global labor mobility, particularly given the complexity of challenges encompassing legal, social, economic, and cross-border governance dimensions. Although Indonesia has ratified the 1990 Migrant Workers Convention through Law No. 6 of 2012 and enacted Law No. 18 of 2017 on the Protection of PMI, the implementation of such protections continues to face significant obstacles. This study aims to analyze the effectiveness of legal protection for PMI, including non-procedural workers and their family members, as well as to evaluate the role of the state and relevant institutions in ensuring comprehensive protection. Employing a normative juridical method, data were collected through document analysis and literature review. The findings reveal a gap between the existing legal framework and its implementation, as evidenced by weak inter-agency coordination, limited diplomatic capacity, and low levels of legal literacy among prospective migrant workers. Furthermore, contemporary issues such as covert human trafficking, violations of migrant workers’ children’s rights, and inconsistencies in the enforcement of bilateral MoUs exacerbate the vulnerability of PMI, particularly in the informal sector. This study recommends strengthening community-based protection mechanisms, reforming migration governance, and mainstreaming human rights and gender-sensitive approaches in migration policies.